Diseño e implementación de un sistema eléctrico inteligente, en una oficina modelo basada en la aplicación de la domótica para el mejoramiento de la eficiencia energética y el confort - Chicaiza Rodríguez, Cristian Geovanny (2016)
The smart or most known electrical systems and home automation applied to offices, house, industry, and others are future technologies, highly advanced that allows users to interact with their home remotely from any place that the owner is, providing security, comfort and energy efficiency, an intelligent system is able to collect information from sensors or inputs, processing and issue orders to actuators or outputs….